THE IMPACT OF INCOTERMS 2020 RULES ON THE DEVELOPMENT OF INTERNATIONAL TRADE - Suyunov Abdunor Miltikbaevich; Fakhriddinova Rushana Fakhriddin Kizi (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the reforms carried out in the development of Customs affairs, the general situation of the application of Incoterms delivery conditions, the impact of the application and problems encountered by the general rules when applying the general rules of Incoterms in foreign economic activity, prospects for the transportation of goods through sea routes when exporting or importing goods to Uzbekistan.